Efektivitas Pendekatan Creative Problem Solving (CPS) dalam Meningkatkan Kemampuan Menemukan Ide Inovatif Topik Penelitian Mahasiswa Pendidikan Biologi - Nurrijal, Nurrijal (Program Studi Pendidikan Biologi FKIP Uniiversitas Muhammadiyah Luwuk, 2024)
This study aims to analyze the effectiveness of implementing the Creative Problem Solving (CPS) approach in enhancing the ability of biology education students to generate innovative ideas for their thesis research topics. The research employed a pre-experimental design with a one-shot case study model. The subjects consisted of 73 fifth-semester students from the Biology Education Department, FKIP, Halu Oleo University. Data were collected through creative portfolio assessments and student response questionnaires. The creative portfolio assessment measured the novelty, creativity, and relevance of students' research ideas, while the questionnaire gathered student perceptions regarding the implementation of CPS. The results showed that the CPS approach effectively improved students' ability to generate innovative, original, and relevant research ideas. Students who participated in CPS-based learning were able to identify and formulate research problems more systematically, explore literature sources effectively, and produce high-quality research proposals. Additionally, the questionnaire results indicated that most students responded positively to the CPS method, as it was perceived to motivate, stimulate creative thinking, and provide practical solutions for addressing research challenges. Thus, the CPS approach can be implemented as an effective teaching strategy to support the development of students' creative and critical thinking skills, while contributing to the improvement of research quality in biology education.